PERAN LITERASI KELUARGA DALAM PENGEMBANGAN KETERAMPILAN MEMBACA ANAK SEKOLAH DASAR - Risa Ardila sari Sahwan; Haifaturrahmah Haifaturrahmah; Nursina Sari (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to systematically examine the role of family literacy in developing the reading skills of elementary school students. The research employed a Systematic Literature Review (SLR) approach by analyzing national and international studies published between 2015 and 2025. Literature sources were obtained from Google Scholar, DOAJ, Scopus, and the Garuda Portal databases using the keywords “family literacy,” “reading skills,” “parental involvement in reading,” and “elementary school students.” The findings indicate that family literacy has a significant impact on improving several aspects of children’s reading skills, including reading interest, motivation, comprehension, and fluency. The most effective forms of family involvement include shared reading activities, establishing daily reading routines at home, providing reading materials, and offering emotional support for children. However, the effectiveness of family literacy is influenced by supporting factors such as parental knowledge, available time, and school support, while it is often hindered by economic constraints and limited access to reading materials. Therefore, this study emphasizes the importance of collaboration among families, schools, and the government to strengthen sustainable home-based literacy ecosystems as an integral part of national literacy policies.